2006
DOI: 10.1158/0008-5472.can-06-1576
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chemical Inhibitor of the Oncogenic Transcription Factor Forkhead Box M1

Abstract: The oncogenic transcription factor forkhead box M1 (FoxM1) is overexpressed in a number of different carcinomas, whereas its expression is turned off in terminally differentiated cells. For this reason, FoxM1 is an attractive target for therapeutic intervention in cancer treatment. As a first step toward realizing this goal, in this study, using a high-throughput, cellbased assay system, we screened for and isolated the antibiotic thiazole compound Siomycin A as an inhibitor of FoxM1. Interestingly, we observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
229
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(246 citation statements)
references
References 27 publications
14
229
1
2
Order By: Relevance
“…Similarly in our study, we investigated the effects of dexamethasone and siomycin A on T-ALL cells and found that dexamethasone and siomycin A alone or in combination caused a significant reduction in gene expression levels of FoxM1 in a dose-dependent manner. Besides causing down-regulation of FoxM1, siomycin A has also been known to reduce the mRNA and protein levels of this transcription factor [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in our study, we investigated the effects of dexamethasone and siomycin A on T-ALL cells and found that dexamethasone and siomycin A alone or in combination caused a significant reduction in gene expression levels of FoxM1 in a dose-dependent manner. Besides causing down-regulation of FoxM1, siomycin A has also been known to reduce the mRNA and protein levels of this transcription factor [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Siomycin A was identified as a strong proapoptotic compound in epithelial cells and also as a potential anticancer drug that causes apoptosis and induces lysosomal membrane permeabilisation [21]. Siomycin A has been shown to downregulate the transcriptional activity and also the protein and mRNA levels of FoxM1 in human cancer cell lines [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…FOXM1 has been reported previously to be a valid therapeutic target in cancer (25); the use of a cell-penetrating ARF peptide inhibitor of FOXM1 has been shown to selectively induce apoptosis in human hepatocellular carcinoma cell lines and mouse models (14). In addition, a related antibiotic thiazole compound, siomycin A, has been reported to downregulate the transcriptional activity and expression of FOXM1 (26). It is interesting to note that Radhakrishnan et al have shown that overexpression of wild-type FOXM1 is sufficient to block the antiproliferative effects of thiostrepton, whereas we found here that only expression of a constitutively active DN-FOXM1, but not the wild-type FOXM1, can rescue cells from the antiproliferative effects of thiostrepton.…”
Section: Discussionmentioning
confidence: 99%
“…Amsacrine also further increased GFP-LC3 puncta in the presence of BafA1 (Supplementary Figure 2C and D). By contrast, siomycin-A (which is a putative FoxM1 inhibitor) (Radhakrishnan et al, 2006) failed to induce autophagy and rather inhibited fusion between GFP-LC3 þ and LAMP2 þ vacuoles, indicating that it prevented the fusion between autophagosomes and lysosomes (which is also inhibited by the vacuolar ATPase inhibitor, BafA1) (Supplementary Figure 2A-D). These results underscore the necessity of carefully measuring autophagic flux to distinguish inducers of autophagy from blockers of the last steps of autophagic turnover.…”
Section: A Chemical Compound Screen For Simultaneous Detection Of Autmentioning
confidence: 99%